Ocean Wave Characteristics in Indonesian Waters for Sea Transportation Safety and Planning - Kurniawan, Roni; Khotimah, Mia Khusnul (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2015)
This study was aimed to learn about ocean wave characteristics and to identify times and areas with vulnerability to high waves in Indonesian waters. Significant wave height of Windwaves-05 model output was used to obtain such information, with surface level wind data for 11 years period (2000 to 2010) from NCEP-NOAA as the input. The model output data was then validated using multimission satellite altimeter data obtained from Aviso. Further, the data were used to identify areas of high waves based on the high wave’s classification by WMO. From all of the processing results, the wave characteristics in Indonesian waters were identified, especially on ALKI (Indonesian Archipelagic Sea Lanes). Along with it, which lanes that have high potential for dangerous waves and when it occurred were identified as well. The study concluded that throughout the years, Windwaves-05 model had a magnificent performance in providing of ocean wave characteristics information in Indonesian waters. The information of height wave vulnerability needed to make a decision on the safest lanes and the best time before crossing on ALKI when the wave and its vulnerability is likely low. Throughout the years, ALKI II is the safest lanes among others since it has been identified of having lower vulnerability than others. The knowledge of the wave characteristics for a specific location is very important to design, plan and vessels operability including types of ships and shipping lanes before their activities in the sea